Criminal Responsibility Towards Public Transportation Company If Traffic Accidents Based On Law Number 22 Of 2009 Concerning Traffic And Road Transport - David David; Faisal Santiago (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
The number of accidents caused by public transportation and no concrete responsibility for the entrepreneur / owner of public transportation, the absence of strict sanctions against the owner or entrepreneur of public transportation in the event of a traffic accident, and there is no legal protection for passengers or family of passengers who are victims of accidents traffic on public transport. In the event that a traffic crime is committed by a Public Transportation Company, in addition to the punishment imposed on the management as referred to in paragraph (1), a maximum fine of 3 (three) times the fines specified in each article in this Chapter shall also be imposed. In addition to fines, public transportation companies can be subject to additional penalties in the form of temporary suspension or revocation of the transportation operation permit for the vehicles used. However, the police cannot immediately revoke the license to operate public transport whose fleets have experienced traffic accidents.Problem Statements: how sanctions against public transportation companies in the event of a traffic accident based on Law Number 22 of 2009 concerning Road Traffic and Transportation? Methodology: In this journal, the author uses a type of empirical research, namely research conducted through field studies that examines (especially) primary data which is also complemented by materials in the form of legislation and research results, assessment results and other references. Significance and contribution of the study: sanctions against public transportation companies in the event of a traffic accident based on Law Number 22 of 2009 concerning Road Traffic and Transportation